The influences of electronic word of mouth towards consumer purchasing behavior / Ain Nabila Misran Farah and Syahidah Norjai - Misran, Ain Nabila; Norjai, Farah Syahidah (Faculty of Business Management, 2016)
From years to years word of mouth has been very effective tool in marketing of business services. Recently due to the advancement of information technology it has given an even more powerful edge for this tool. This research reflects upon this new development of electronic word of mouth and assesses its influence on customers purchasing decisions. The influence of electronic word of mouth (eWOM) on consumer intention has been known for a long time. This new way of communication might be more powerful in triggering purchasing behavior. This study has examined the influence of information influence, reviewer credibility, participation and persuasiveness of electronic word of mouth towards consumer purchasing behavior.From the findings it can be concluded that research objectives have been achieved. The result indicated that information influences, review credibility, participation and persuasiveness were significantly influences consumer purchasing behavior while the most important factor that influence consumer purchasing behavior is persuasiveness.